Urban green roofs can support a diversity of parasitoid wasps - Diethelm, Aramee C.; Masta, Susan E. (Frontiers in Ecology and Evolution, 2022)
Green roofs are often installed atop buildings to provide ecological services such as mitigating storm water runoff and cooling air within urban heat islands. We found that green roofs in Portland, Oregon, also can support biodiversity, including a diverse assemblage of parasitoid wasps, with 20 morphospecies from nine families present on the four roofs we surveyed. The roofs with greater plant diversity and structural complexity harbored comparatively more parasitoid morphospecies than the structurally simpler Sedum-dominated roofs. The oldest green roof supported much greater diversity than the younger roofs, including a comparably planted roof three times its size. Parasitoid wasps from the Hymenopteran families we found are high-trophic-level organisms known to feed on a variety of arthropods, including many insects commonly considered to be pests in urban areas. We suggest that green roofs have the potential to provide an often-overlooked ecological service by supporting parasitoid wasps that can act as natural biological control agents.